A decollette journal for the Ottoman Turkish women: "Süs" (16 June 1339 (1923)- 26 July 1340 (1924) - Çon, Esra. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2007., 2007)
The publication of women-oriented class journals, which was initiated within the last period of the Ottoman Empire and accelerated during the Second Constitutional Period, was pursued in the first years of the Turkish Republic as well. Women’s journals published within this period can be reckoned as the descendants of those published in the Ottoman Period. The features of these women’s journals published within the early republican period e.g. the content, the style, and the topics discussed as well as the editorial staff, reinforce the said argument. Süs is a women’s journal published precisely during this process of transition (1923-1924). Covering both literary knowledge and useful practical information in an intellectual and entertaining content, Süs can be considered as rich within this respect. On the other hand, the diversity of the content and the object to keep an equal distance between all of these different elements brings forth the idea that the journal was published in accordance with commercial motives rather than an intellectual mission. Because the more diversified the content is the more different reader’s mass it will address to. Furthermore, the actual target mass of the journal is observed to be the educated young girls. Considering the fact that, the majority of the editorial staff was experienced literary people and the people who were previously engaged in publication of various magazines, Süs can be evaluated respectively successful in terms of anticipating the overall tendency of the target mass and preparing a relevant content that appeals to them. One of the most significant objectives of this thesis is to obtain an opinion about the agenda, interests and intellectual worlds of the target mass of Süs, which was skillfully issued with commercial motives, namely the educated young girls who used to live in İstanbul or other big cities between 1923 and 1924. Moreover, this study is aimed to discuss the women’s issues and the remarkable women’s movements of the related period through the perspective of an Ottoman women’s journal.
Keywords: Women's periodicals, Turkish.; Women -- Turkey -- History.; Women -- Turkey -- Social conditions -- History.